Language: More than a Mechanism for Communication - Miranda Calderón, Luis Alfredo (2011)
The objective of this paper is to study the importance of language in the learning process of individuals, in contrast to the traditional view that has predominated in the teaching of language and its incidence in the educational field. An analysis is performed from the different perspectives of experts who have studied the language, its learning implications and language development of individuals throughout their lives. This paper brings up the need to establish pedagogical mechanisms to approach a new vision in the teaching of language in any area, considering language as a tool for learning and as a way to reach full expression in all forms of education.